Fertility Choice in a Model of Economic Growth - Barro, Robert J.; Becker, Gary S. (Econometrica, 1989)
Altruistic parents make choices of family size along with decisions about consumption and intergenerational transfers. The authors apply this framework to a closed economy, where the determination of interest rates and wage rates is simultaneous with the determination of population growth and the accumulation of capital. Thus, they extend the literature on optimal economic growth to allow for optimizing choices of fertility and intergenerational transfers. The authors use the model to assess the effects of child-rearing costs, the tax system, the conditions of technology and preferences, and shocks to the initial levels of population and the capital stock. Copyright 1989 by The Econometric Society.